Residential radon and lung cancer--detailed results of a collaborative analysis of individual data on 7148 persons with lung cancer and 14,208 persons without lung cancer from 13 epidemiologic studies in Europe. - Darby, S; Hill, D; Deo, H; Auvinen, A; Barros-Dios, J; Baysson, H; Bochicchio, F; Falk, R; Farchi, S; Figueiras, A; Hakama, M; Heid, I; et al. (2006)
OBJECTIVES: Studies seeking direct estimates of the lung cancer risk associated with residential radon exposure lasting several decades have been conducted in many European countries. Individually these studies have not been large enough to assess moderate risks reliably. Therefore data from all 13 European studies of residential radon and lung cancer satisfying certain prespecified criteria have been brought together and analyzed. METHODS: Data were available for 7148 persons with lung cancer and 14,208 controls, all with individual smoking histories and residential radon histories determined by long-term radon gas measurements. RESULTS: The excess relative risk of lung cancer per 100 Bq/m3 increase in the observed radon concentration was 0.08 [95% confidence interval (95% CI) 0.03-0.16; P=0.0007] after control for confounding. The dose-response relationship was linear with no evidence of a threshold, and it remained significant when only persons with observed radon concentrations of <200 Bq/m3 were included. There was no evidence that the excess relative risk varied with age, sex, or smoking history. Removing the bias induced by random uncertainties related to radon exposure assessment increased the excess relative risk of lung cancer to 0.16 (95% CI 0.05-0.31) per 100 Bq/m3. With this correction, estimated risks at 0, 100, and 400 Bq/m3, relative to lifelong nonsmokers with no radon exposure, were 1.0, 1.2, and 1.6 for lifelong nonsmokers and 25.8, 29.9, and 42.3 for continuing smokers of 15-24 cigarettes/day. CONCLUSIONS: These data provide firm evidence that residential radon acts as a cause of lung cancer in the general population. They provide a solid basis for the formulation of policies with which to manage risk from radon and reduce deaths from the most common fatal cancer in Europe.